Discontent against missions, but peace in Canton (1900)
This collection of diplomatic dispatches from the Portuguese Consulate in Canton, dated between August and September 1900, comprises official correspondence concerning political instability and revolutionary activity in southern China during the late Qing period. The documents include telegraphic reports from the Governor of Chacan, communications from Tê, Acting Viceroy of Canton, and exchanges between the Portuguese Consul (J.M. Lopes), the Governor of Macau (Dr. Horta e Costa), and the Portuguese Minister of Foreign Affairs. Central to the correspondence is an alleged conspiracy by the ‘Protectorate Party of the Empire’—a revolutionary faction linked to secret societies such as the Se Kung-in-vai and Wang—and its coordination with exiled reformers including Kang Youwei. The Viceroy reports on plans for insurrection across Liang-hue, San Chiang, and Liang-pang provinces, detailing arms smuggling via Nan-yang (interpreted as the Southern Seas), recruitment networks in Hong Kong and Macau, and the involvement of key figures such as Ho-lin-wong, Tao-Cheng-pat, and Chang Chong-im. British diplomatic responses, particularly from the Hong Kong authorities, are noted, highlighting tensions between colonial protection of dissidents and Qing demands for repression. The Consul assesses the feasibility of revolt, regional security measures, and fears of assassination against high-ranking officials. These documents provide critical insight into Sino-foreign relations, transregional revolutionary networks, and colonial diplomacy in South China at the turn of the 20th century.
Keywords: Acting Viceroy of Canton communications; Arms Smuggling; British diplomatic responses; Canton regional governance; Chang Chong-im; Consul J.M. Lopes; Cross-Border Conspiracy Theories; Exiled Reformers; Governor of Chacan reports; Governor of Macau Dr. Horta e Costa; Ho-lin-wong; Hong Kong recruitment networks; Kang Youwei; Late Qing revolutionary activity; Macau intelligence channels; Nan-yang region; Political Instability Southern China; Portuguese Consulate in Canton; Protectorate Party of the Empire; Qing Dynasty diplomatic correspondence; Qing government security measures; Se Kung-in-vai; Tao-Cheng-pat; Transcription; Wang secret society; official Portuguese archives